(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
Study This aim for analyze influence style leadership, job crafting, work discipline, and employee creativity to performance employee (study case of BKPP Semarang City). The approach used in this research this is the method quantitative , with collected data through questionnaire . Population study This covers all over Semarang City BKPP employees , while samples taken​ totaling 100 respondents . Retrieval technique sample done use non-probability sampling method with saturated sampling approach . Data analysis in research This use device SPSS software version 26 for test hypothesis that has been formulated . Research results show that, Leadership Style No influential significant to performance employee with mark of 0.116 > 0.050, Job Crafting has an effect significant to performance employee with mark of 0.005 < 0.05, Work discipline has an effect significant to performance employee with mark of 0.052 > 0.05, and employee creativity has an influence significant to performance employee with mark of 0.004 < 0.05.